Differentiation Learning to Improve Students Potential in Elementary School - MS Zulela; Edwita Edwita; Yuli Mulyawati (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
Student potential is the capacity or ability and characteristics/nature of individuals related to human resources that have the possibility to be developed and or support the development of other potentials contained in students. In the process of implementing learning today, many teachers have not implemented differentiation learning so many students have not developed their potential. The purpose of this study was to determine the learning of differentiation can increase the potential of students in elementary schools. The method used in this study is that literature review is research that examines or critically reviews the knowledge, ideas, or findings contained in the academic-oriented literature, as well as formulating theoretical and methodological contributions to certain topics. The results showed that differentiation is to provide opportunities for students to show what students understand. Also, in this way the teacher can find out what method should be given to students whose grasping power is lacking, sufficient and good. By understanding the potential of students, teachers can give an accurate picture of their strengths and weaknesses, the strengths and weaknesses of students, and can identify potentials that need to be improved and weaknesses that need to be minimized. With differentiation learning, it guides students in increasing the potential that exists within themselves. The conclusion of the teacher must be able to guide students to be able to develop according to their characteristics, and the potential possessed by these students, this is closely related to differentiated learning. One of the values and roles of teachers is to create learning that favors students, namely learning that liberates students' thinking and potential. Differentiation can be implemented in the content, process, and product of learning.